Improving consensus development for health technology assessment : an international perspective - Goodman, Clifford; Baratz, Sharon R. (Council on Health Care Technology, Institute of Medicine, National Academy Press, 1990)
Considers medical technology consensus development programs in Canada, Denmark, Finland, Netherlands, Norway, Sweden, England and the United States.